2015
DOI: 10.1002/2014gc005645
|View full text |Cite
|
Sign up to set email alerts
|

Along‐axis variation in crustal thickness at the ultraslow spreading Southwest Indian Ridge (50°E) from a wide‐angle seismic experiment

Abstract: The Southwest Indian Ridge (SWIR) is characterized by an ultraslow spreading rate, thin crust, and extensive outcrops of serpentinized peridotite. Previous studies have used geochemical and geophysical data to suggest the presence of a thicker crust at the central and shallowest portions of the SWIR, from the Prince Edward (35 30 0 E) to the Gallieni (52 20 0 E) fracture zones. Here we present a new analysis of wide-angle seismic data along the ridge 49 17 0 E-50 49 0 E. Our main conclusions are as follows: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
60
0
9

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 79 publications
12
60
0
9
Order By: Relevance
“…Anomalously shallow ridge flanks were interpreted to indicate a dramatic increase in magma supply since 8–10 Ma [ Sauter et al ., , ] and that it is characterized by robust magmatism with abundant basalts at the seabed [ Sauter et al ., ], and without peridotites [ Zhou and Dick , ]. The only axial high exists along segment 27 (~50°28′E), a 72 km long segment where the axial depth is on average 1000 m shallower than nearby ridge segments (Figure a) and numerous volcanic edifices are present on both flanks of the axial valley, with relatively flat topography to the north and greater relief to the south (Figure b) [ Niu et al ., ]. Segment 27 shows a pronounced MBA low and a large negative anomalies of S wave velocities at depth [ Sauter et al ., ], with anomalously thick crust of up to 10 km at the segment center [ Niu et al ., ] and off axis within a 20 km distance [ Li et al ., ].…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Anomalously shallow ridge flanks were interpreted to indicate a dramatic increase in magma supply since 8–10 Ma [ Sauter et al ., , ] and that it is characterized by robust magmatism with abundant basalts at the seabed [ Sauter et al ., ], and without peridotites [ Zhou and Dick , ]. The only axial high exists along segment 27 (~50°28′E), a 72 km long segment where the axial depth is on average 1000 m shallower than nearby ridge segments (Figure a) and numerous volcanic edifices are present on both flanks of the axial valley, with relatively flat topography to the north and greater relief to the south (Figure b) [ Niu et al ., ]. Segment 27 shows a pronounced MBA low and a large negative anomalies of S wave velocities at depth [ Sauter et al ., ], with anomalously thick crust of up to 10 km at the segment center [ Niu et al ., ] and off axis within a 20 km distance [ Li et al ., ].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The only axial high exists along segment 27 (~50°28′E), a 72 km long segment where the axial depth is on average 1000 m shallower than nearby ridge segments (Figure a) and numerous volcanic edifices are present on both flanks of the axial valley, with relatively flat topography to the north and greater relief to the south (Figure b) [ Niu et al ., ]. Segment 27 shows a pronounced MBA low and a large negative anomalies of S wave velocities at depth [ Sauter et al ., ], with anomalously thick crust of up to 10 km at the segment center [ Niu et al ., ] and off axis within a 20 km distance [ Li et al ., ]. The thick oceanic crust indicates robust magma supply in this area, which has been inferred to be associated with the Crozet hotspot [ Sauter et al ., ; Zhang et al ., ].…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Such style of heat source can contribute to continuous hydrothermal activity for over 1000 years. Duanqiao field is located near the central volcano and there is a hot mantle and/or fertile melt beneath Duanqiao field (Tao et al 2012;Niu et al 2015). The crust thickness is 9.5 km, suggesting the existence of AMC (Axial Magma Chamber) which provides magma source to the field Mendel et al 2003).…”
Section: Episodes Of Hydrothermal Activitymentioning
confidence: 99%
“…Li et al (2015) used three-dimensional seismic tomography at 50°28 0 E and revealed a low-velocity anomaly (*0.6 km/s) which was accompanied by an unusually thick crust (*9.5 km). Niu et al (2015) also identified the thick crust (*10 km) beneath the segment center by wide-angle seismic reflection. Li et al (2013) reported the geochemical and molecular biological compositions of low-temperature hydrothermal deposits.…”
Section: Introductionmentioning
confidence: 99%